Moisture-driven shifts in microbial nitrogen limitation under biochar and nitrification inhibitors co-application in tropical soils - Lijun Liu; Qilin Zhu; Xiaoqian Dan; Huanyu Bao; Tongbin Zhu; Lei Meng; Ahmed S. Elrys; Christoph Müller; Jinbo Zhang (Geoderma, 2025)
Biochar and nitrification inhibitors (NIs) are crucial in improving soil nitrogen (N) availability and decreasing its environmental consequences in agroecosystems. Soil microbes can regulate soil N dynamics through metabolic processes, such as the secretion of extracellular enzymes, which affect both N production and turnover. However, how and why soil microbial N limitation (MNL) responds to biochar-NIs co-application is poorly understood, especially in tropical regions under different moisture contents. Here, an incubation study was conducted on soils from a long-term rice-vegetable rotation to investigate the effects of five treatments including control (no biochar or NIs), 2 % biochar, 2 % biochar plus 5 % dicyandiamide (DCD), 2 % biochar plus 1 % 3,4 dimethylpyrazole phosphate (DMPP), and 2 % biochar plus 2.5 % DCD and 0.5 % DMPP, at 60 % and 100 % water holding capacity (WHC) on MNL and N availability. Biochar derived from rice straw was applied at a rate of 40 Mg ha−1. All treatments, including the control, received 150 mg N kg−1 as urea, with NIs added proportionally to the applied N mass. The vector-threshold element ratio was applied to evaluate MNL, while δ15N and net N transformation rates were measured to evaluate N availability. The vector-threshold model results indicated severe MNL in studied soils, and that biochar, alone or with NIs, increased δ15N and alleviated the MNL under unsaturated conditions, while the opposite was observed under saturated conditions. Biochar increased the particulate and dissolved organic carbon contents, which in turn increased the net N mineralization rate, thereby alleviating MNL under unsaturated conditions. Relative to biochar, biochar-NIs co-application increased net N mineralization rate under unsaturated conditions. The lower nitrate production in response to biochar, alone or with NIs, decreased δ15N and aggravated MNL under saturated conditions. Among all NIs treatments, biochar + DMPP showed the highest net N mineralization rate, but the lowest MNL at 60 % WHC and the highest MNL at 100 % WHC. Nitrous oxide emissions increased in response to biochar alone, but decreased under biochar-NIs co-application in unsaturated and saturated soils, with the lowest emissions observed for biochar + DCD at 60 % WHC and biochar + DCD + DMPP at 100 % WHC. Our results indicated that soil moisture conditions control the response of MNL and N losses to biochar and NIs in the tropics.